A Custom-Made Device for Reproducibly Depositing Pre-metered Doses of Nebulized Drugs on Pulmonary Cells in vitro - Horstmann, Justus C.; Thorn, Chelsea R.; Carius, Patrick; Graef, Florian; Murgia, Xabier; de Souza Carvalho-Wodarz, Cristiane; Lehr, Claus-Michael (Frontiers in Bioengineering and Biotechnology, 2021)
The deposition of pre-metered doses (i.e., defined before and not after exposition) at the air–liquid interface of viable pulmonary epithelial cells remains an important but challenging task for developing aerosol medicines. While some devices allow quantification of the deposited dose after or during the experiment, e.g., gravimetrically, there is still no generally accepted way to deposit small pre-metered doses of aerosolized drugs or pharmaceutical formulations, e.g., nanomedicines. Here, we describe a straightforward custom-made device, allowing connection to commercially available nebulizers with standard cell culture plates. Designed to tightly fit into the approximately 12-mm opening of either a 12-well Transwell® insert or a single 24-well plate, a defined dose of an aerosolized liquid can be directly deposited precisely and reproducibly (4.8% deviation) at the air–liquid interface (ALI) of pulmonary cell cultures. The deposited dose can be controlled by the volume of the nebulized solution, which may vary in a range from 20 to 200 μl. The entire nebulization-deposition maneuver is completed after 30 s and is spatially homogenous. After phosphate-buffered saline (PBS) deposition, the viability and barrier properties transepithelial electrical resistance (TEER) of human bronchial epithelial Calu-3 cells were not negatively affected. Straightforward in manufacture and use, the device enables reproducible deposition of metered doses of aerosolized drugs to study the interactions with pulmonary cell cultures grown at ALI conditions.